Melanin is effective in protecting fast and slow growing fungi from various types of ionizing radiation. (22nd February 2017) - Pacelli, Claudia; Bryan, Ruth A.; Onofri, Silvano; Selbmann, Laura; Shuryak, Igor; Dadachova, Ekaterina
Summary: Melanin is a ubiquitous pigment with unique physicochemical properties. The resistance of melanized fungi to cosmic and terrestrial ionizing radiation suggests that melanin also plays a pivotal role in radioprotection. In this study, we compared the effects of densely‐ionizing deuterons and sparsely‐ionizing X‐rays on two microscopic fungi capable of melanogenesis. We utilized the fast‐growing pathogenic basiodiomycete forming an induced DOPA‐melanin, Cryptococcus neoformans (CN); and the slow‐growing environmental rock‐inhabiting ascomycete synthesizing a constitutive DHN‐melanin, Cryomyces antarcticus (CA); melanized and non‐melanized counterparts were compared. CA was more resistant to deuterons than CN, and similar resistance was observed for X‐rays. Melanin afforded protection against high‐dose (1.5 kGy) deuterons for both CN and CA ( p ‐values < 10 −4 ). For X‐rays (0.3 kGy), melanin protected CA ( p ‐values < 10 −4 ) and probably CN. Deuterons increased XTT activity in melanized strains of both species, while the activity in non‐melanized cells remained stable or decreased. For ATP levels the reverse occurred: it decreased in melanized strains, but not in non‐melanized ones, after deuteron exposure. For both XTT and ATP, which reflect the metabolic activity of the cells, larger and more statistically‐significant differences as a function of melanization status occurred in CN. Our data show, for the first time, that melanin protected both fast‐growing and slow‐growing fungi from high doses of deuterons under physiological conditions. These observations may give clues for creating melanin‐based radioprotectors.